⁠ The Importance of Scientific Integrity for the Improvement of University Level Learning - Iryna Tymchenko; Ihor Danyliuk; Mykola Yaroshov; Roksolana Yaremkevych; Svitlana Demikhova (Revista on line de Política e Gestão Educacional)
The study focuses on the concept of higher education development in terms of academic integrity. The article aims to analyze the role of technology in creating a unique text within scientific communication in the current information space. The functionality of scientific communication in higher education is substantiated. The trends in the development of modern models of scientific communication are highlighted. The specifics of innovative approaches to creating a unique scientific text are investigated. The problems of the life cycle of electronic resources and related risks are studied. The principles of the Bucharest Declaration on Ethical Values and Principles of Higher Education in the European Region are analyzed. The directions for improving scientific communication processes in higher education are defined. The article demonstrates that the development of the educational environment in the modern, globalized scientific field necessitates the optimization of specific requirements for creating a unique text based on the principles of originality and integrity.